Perbedaan Hasil Pemeriksaan Tajam Penglihatan dan Refraksi pada Anak Usia 4-12 tahun pada Pemeriksaan Non Sikloplegik dan Sikloplegik - Sawitri Boengas; Rivan Virlando Suryadinata (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2022)
ABSTRACTBackground of Study: Globally,  there are 19 million children with visual impairment, 12 million are caused by uncorrected refractive errors. Uncorrected refractive errors in children have the potential to cause amblyopia, severe visual impairment and even blindness. Refractive errors in children must receive proper management. Cycloplegic refraction is a gold standart method for children to minimize the effect of strong accommodation in childhood. The purpose of the study: to analyze the differences between the results of the visual acuity examination and refractive examination between the non-cycloplegic and the cycloplegic examination in children aged 4-12 years. Methods: This study is an analytical observational study through recording medical records of patients 4-12 y.o between November 2020-October 2021, which were carried out with non-cycloplegic and cycloplegic refraction. Data were analyzed by SPSS with WilcoxonTest. Results: There were 106 eyes of children consisting of 62(58%) boys and 44(42%) girls. Based on statistical tests, there was no difference in natural visual acuity on non-cycloplegic and cycloplegic examinations. There were differences between non-cycloplegic and cycloplegic refractions. The difference in refraction results towards the positive spherical 75(70,75%) children towards the negative spherical 21(19.81%) children, only 10(9,4%) children showed the same results between the two refractive stages. Conclusion: There was no difference in children's visual acuity between the non-cycloplegic examination and the cycloplegic examination, but there were differences in the results of non-cycloplegic and cycloplegic refraction in children aged 4-12 years. Therefore, the determination of the size of the glasses in children must be done through cycloplegic refraction.Keywords : Refraction, Cycloplegic Refraction, Visual Acquity, Children